2010
DOI: 10.1177/0731684409349929
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Experimental Parameters in the Microbond Test with Regard to Lyocell Fibers

Abstract: Microbond technique is used to measure the interfacial shear strength (IFSS) of cellulose fiber-reinforced composites. Critical aspect ratios are provided for a variety of cellulose fiber-polymer matrix systems to avoid the fiber breakage during microbond test. The influence of fiber cross-section and droplet curing condition on the force-displacement curve and the corresponding change of IFSS are discussed for lyocell-polypropylene system. Finally, a relationship between the contact angle of a polymer drop on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…viscose) to the hydrophobic matrix polymer such as polypropylene (PP) is a significant drawback that hampers extended use of these fibres (Albano et al 1999). Several authors reported interfacial shear strengths (IFSS) between regenerated cellulose fibres and polyethylene (PE) and polypropylene (PP) in the range of 3-8.8 MPa based on fragmentation and microbond tests (Adusumalli et al 2006(Adusumalli et al , 2010Karlsson et al 1996;Awal et al 2011;Müssig and Graupner 2017).…”
Section: Introductionmentioning
confidence: 99%
“…viscose) to the hydrophobic matrix polymer such as polypropylene (PP) is a significant drawback that hampers extended use of these fibres (Albano et al 1999). Several authors reported interfacial shear strengths (IFSS) between regenerated cellulose fibres and polyethylene (PE) and polypropylene (PP) in the range of 3-8.8 MPa based on fragmentation and microbond tests (Adusumalli et al 2006(Adusumalli et al , 2010Karlsson et al 1996;Awal et al 2011;Müssig and Graupner 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, individual laboratories tend to create their own methods with essentially the same idea but different procedures. Although the application of MBT to thermosetting composites has attracted a great deal of attention over the years [4,[12][13][14][15], it has been, to a lesser extent, considered for thermoplastic systems [16][17][18]. As a result, the procedure for using this method with thermoplastic polymers needs to be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the work carried out on adhesion analysis between a plant fiber and a polymer matrix are often satisfied by the determination of an apparent interfacial shear stress and do not take in account the stiffness of the interphase. [12][13][14][15][16][17][18] The interphase plays a crucial role in the charge transfer and the toughness of the prepared composite.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated the influence of the complex structure of the plant fibers on the adhesion properties to polymer matrices. Most of the work carried out on adhesion analysis between a plant fiber and a polymer matrix are often satisfied by the determination of an apparent interfacial shear stress and do not take in account the stiffness of the interphase . The interphase plays a crucial role in the charge transfer and the toughness of the prepared composite.…”
Section: Introductionmentioning
confidence: 99%